BOOK REVIEW: Mental Disorders And The Law By Kok Lee Peng, Molly Cheang And Chee Kuan Tsee - Talib, Norchaya (Journal of Malaysian and Comparative Law, 2019)
The book is divided into five parts. Part I describes mental disorders and gives an account of the existing mental health laws in Singapore and Malaysia, in one chapter. The first half of Chapter One explains what is meant by mental disorder; taking the reader through a detailed yet concise route of the nature of psychiatric problems, problems in terminology and the classfications of mental disorder - all these are rather technical and clinical in expression. The processes that a medical expert has to go through in relation to a mentally disordered accused or defendant before giving evidence are also explained here.